2018
DOI: 10.1016/j.yexcr.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Connections of annexin A1 and translocator protein-18 kDa on toll like receptor stimulated BV-2 cells

Abstract: exogenous ANXA1 down-modulates LPS-induced TSPO via MyD-88/NF-κB pathways, and constitutive TSPO is pivotal for the control of ANXA1 on TNFα secretion. TSPO actions may be involved with the mechanisms of ANXA1 on inflammatory brain diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
3
1
Order By: Relevance
“…Indeed, our results showed that FPR2/3 knockout mice and pharmacological inhibition of FPR2 by using WRW4 led not to inhibition but an increase of the levels of IL‐1β. In fact, exogenous AnxA1 acting on FPR2 may downmodulate the Myd88/NFκB pathway and downregulate IL‐1β secretion, 50 although we found here that pre‐treatment of BMDMs with Ac2‐26 had no effect on IL‐1β release.…”
Section: Discussioncontrasting
confidence: 74%
“…Indeed, our results showed that FPR2/3 knockout mice and pharmacological inhibition of FPR2 by using WRW4 led not to inhibition but an increase of the levels of IL‐1β. In fact, exogenous AnxA1 acting on FPR2 may downmodulate the Myd88/NFκB pathway and downregulate IL‐1β secretion, 50 although we found here that pre‐treatment of BMDMs with Ac2‐26 had no effect on IL‐1β release.…”
Section: Discussioncontrasting
confidence: 74%
“…This is the first direct evidence of annexin A1 overexpression in lymph node metastasis of head and neck cancer. Annexin A1 is a protein involved in inflammation [ 89 ], apoptosis [ 90 ], cell differentiation [ 91 ], migration, invasion [ 92 ], and signaling [ 93 ]. It is a substrate of growth factors and kinases and exhibits abnormal (high or low) levels in several tumors and inflammatory conditions (reviewd by [ 94 – 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow cells, obtained as described above, were incubated in 12-well plates (10 6 cells per well) in the presence or absence of WRW4 (10 μM; Tocris Bioscience, UK), a selective antagonist of FPR2 51,52 , for 1 h. Then, cells were treated with rAnxA1 (100 nM) for 12 h at 37 °C in 5% CO 2 and immunophenotyped as above.…”
Section: Methodsmentioning
confidence: 99%